The Clergymen Should Work in the House of God not in the Parliament – the History of the Józef Putek’s Parliamentary Amendment from 1920 that Deprived the Clergy of their Passive Suffrage - Magiera, Paweł (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
The article presents history of the amendment which was proposed in 1920 as a part of parliamentary project of constitution by deputy Józef Putek, a member of Polish Peasant Party – Left. Through this amendment he wanted to deprive the clergy of all confessions of their passive suffrage to the parliament. The author of this proposition was one of the leading anticlerical deputies in the Legislative Sejm. His idea was a part of the wider discourse of then left-wing parties which sought to eliminate clergy from the public life. This radical concept was not implemented in the constitution and did not lead to the wider discussion in parliament. However, this amendment was an interesting but simultaneously little-known example of the opinions of peasant’s left on the role and relevance of the Catholic Church in the polish society in the beginning of the Second Polish Republic. This topic was not presented so far in a complex way. There were only some short references in a previous literature. Therefore, the article shows comprehensively a history of the Józef Putek’s amendment and the debate about it which took place in the parliament. The article based on historical sources which are stenographic records and documents of the Legislative Sejm (1919–1922). It contains an introduction, main part which is divided into two sections (biography of Józef Putek and then the description of his amendment) and a summary.